INDONESIA’S CRACKDOWN ON RISING ONLINE GAMBLING - Manggala, Bayu Suryadi; Nugroho, Andriyanto Adhi (LPPM STIH Putri Maharaja, 2025)
The rapid rise of online gambling in Indonesia stems from economic hardship, limited legal awareness, and the exploitation of digital technologies for illegal activities. This study aims to examine the accountability of the Ministry of Communication and Digital Affairs (Komdigi) in combating online gambling through a normative juridical approach. The central issue addressed is how Komdigi’s legal authority and strategic role are implemented in managing a secure digital space. The research applies a normative legal method by analysing relevant legislation and administrative practices. Findings indicate that Komdigi has exercised its mandate through AI-based detection systems, public reporting platforms, and inter-agency collaboration with the Financial Services Authority (OJK), the Financial Transaction Reports and Analysis Center (PPATK), and the National Police to block access and take enforcement actions. This research is novel in its mapping of cross-sectoral synergy, reflecting the state's collective effort to combat digital crime. The results show that blocking alone is insufficient, as gambling websites are highly adaptive. It recommends enhancing digital literacy, reinforcing social values, and regularly assessing blocking mechanisms for long-term prevention.